What Veblen taught : - Veblen, Thorstein (A. M. Kelley, Bookseller, 1964)
Contents: This early work is a collection of writings by Thorstein Veblen. Veblen was an American economist and sociologist who wrote both witty critics of the economic status quo and also heavyweight works on the history of economic theory. His best known work was 'The Theory of the Leisure Class.'